ESTETIKA PERTUNJUKAN WAYANG KLITHIK LAKON DAMARWULAN NGRATU SAJIAN KI HADI PURWANTO - Iswara, Danar Yogi; Wicaksono, Andi (Institut Seni Indonesia Surakarta, 2024)
This article discusses the aesthetics of the Wayang Klithik performance Lakon Damarwulan Ngratu presented by Hadi Purwanto. This research uses the aesthetic theory of puppetry namely nuskma and mungguh by Sunardi and is supported by the aesthetic concept of popular puppetry. This research is a qualitative descriptive study. The techniques of data collection consist of observation, interviews and literature study. The analysis is carried out by using a puppetry aesthetic approach that is presented systematically. The result of study were consist of : klithik puppet performered by Ki Hadi Purwanto had nuksma and mungguh esthetic, in the scene of pleasure park’s Blambangan kingdom and Majapahit kingdom. Those scenes also contained local wisdom of Jepara society.